The antibacterial efficacy and effect of tungsten nanoparticles (WO3) on the expression of tetracycline and erythromycin-resistance genes in Streptococcus agalactiae isolated from pregnant women - Salehi, Ava; Rahimi, Mohammad Karim; Bagheri, Fatemeh (GMS Hygiene and Infection Control, 2025)
Background and objectives: Colonization of pregnant women by Streptococcus (S.) agalactiae can lead to intrauterine infections after childbirth and potentially life-threatening infections in newborns. The current effectiveness of available antimicrobials is decreasing, posing a serious threat. Hence, there is an urgent requirement to develop novel categories of antimicrobial agents that can efficiently and swiftly eradicate these infections. To developed new strategies in the management and reduction of infections arising from S. agalactiae, our objective was to evaluate the antibacterial efficacy of tungsten nanoparticles (WO3) on the expression of tetracycline and erythromycin-resistance genes in S. agalactiae isolated from pregnant women. Materials and methods: A total of 46 Group-B streptococcus (GBS) isolates from rectovaginal swabs, blood, and urine cultures were obtained from pregnant women (13–35 weeks gestation) attending Central and Gynecological Hospitals in Tehran, Iran. The identification of GBS isolates was conducted using a variety of routine bacteriological techniques and targeted assays for the molecular characterization of the GBS isolates. The antimicrobial susceptibility test was carried out according to the Kirby-Bauer method. PCR was employed to screen for the presence of tetracycline and erythromycin resistance-associated genes. Tungsten oxide (WO3) nanomaterials were successfully synthesized and characterized using FE-SEM (field emission scanning electron microscopy), and DLS (dynamic light scattering) techniques. The microdilution assay was used to assess the antimicrobial efficacy of WO3 nanostructures. Furthermore, real-time PCR was employed to investigate the effectiveness of WO3 nanostructures in the regulation of the expression of the tetM and ermB resistance genes. Results: The findings of the antibiotic susceptibility assays demonstrated a considerable proportion of S. agalactiae strains with high resistance to tetracycline (87%), erythromycin (71.4%), and clindamycin (63%). Conversely, the resistance rates for chloramphenicol and levofloxacin were 8.7% and 6.5%, respectively. The results of antibiotic susceptibility assays revealed high-resistance S. agalactiae strains to tetracycline (87%), erythromycin (71.4%), and clindamycin (63%), while resistance rates chloramphenicol, levofloxacin, penicillin and ampicillin were 33.3%, 14.8%, 11.1%, and 7.4%, respectively. In addition to the mentioned antibiotics, it is worth noting that all strains exhibited sensitivity to other antibiotics such as ceftriaxone, linezolid, and vancomycin. Of the 24 (88.8%) erythromycin-resistant/intermediate isolates, the ermB gene was found in 16 (66.6%), and the mefA gene in 1 (4.2%) isolates. Furthermore, the tetM and tetO genes were recovered by 83.3% and 4.2% of the tetracycline-resistant isolates, respectively. By utilizing FE-SEM and DLS techniques, it was estimated that the average size of the WO3 nanomaterials were 100 nm and 51.2 nm, respectively. WO3 displayed varying effectiveness against 27 S. agalactiae strains, with minimal inhibitory concentration (MIC) ranging from 500 to 1,000 µg/mL. In addition, the application of nanostructures induced a considerable down-regulation of the antibiotic resistance genes (tetM, ermB) relative to the untreated isolate. Conclusion: The findings indicate that tungsten trioxide nanoparticles hold the potential to serve as a promising pathway for the development of new antibacterial substances, with the specific aim of addressing the problem of antibiotic resistance in infections caused by S. agalactiae.